Pengaruh Model Collaborative Problem Solving Terhadap Kemampuan Pemecahan Masalah Matematis Siswa Ditinjau dari Kemandirian Belajar - Arofah, Rahnis; Ardiyanti, Yusi; Hanifah (Papanda, 2025)
This study aims to analyze the effect of implementing the Collaborative Problem Solving model on students’ mathematical problem-solving abilities, to analyze the effect of learning independence on mathematical problem-solving abilities, as well as to analyze the interaction between the learning model and the level of learning independence. Mathematical problem-solving ability is one of the cognitive skills emphasized in the objectives of mathematics learning. The research approach used in this study is quantitative with an experimental method. The study was conducted at SMP Negeri 6 Karawang Barat in the 2024/2025 academic year. The research sample was selected using purposive sampling, resulting in class VIIC as the control class and class VIID as the experimental class. The instruments used were essay tests to measure mathematical problem-solving abilities and questionnaires to measure learning independence. This research was carried out in three stages: pretest, treatment, and posttest. Data analysis was conducted using the t-test, one-way ANOVA with a 5% significance level, and two-way ANOVA with a 5% significance level. The results of the study indicate that: (1) there is an effect of the Collaborative Problem Solving model on students’ mathematical problem-solving abilities; (2) there is an effect of learning independence on mathematical problem-solving abilities; (3) there is no interaction between the learning model and learning independence on students’ mathematical problem-solving abilities. It can be concluded that the Collaborative Problem Solving model has been proven effective to be applied to students with various levels of learning independence